2000
DOI: 10.1002/1099-0518(20010101)39:1<46::aid-pola50>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Cationic photopolymerization of tetrahydrofuran: A mechanistic study on the use of a sulfonium salt-phenothiazine initiation system

Abstract: The kinetics aspects of the photoinitiated polymerization of tetrahydrofuran with triphenylsulfonium hexafluoroarsenate and sensitized by phenothiazine was studied under visible‐light irradiation. A photosensitizer mechanism was proposed involving electron transfer from phenothiazine to the triphenylsulfonium salt, forming a cation radical, the true precursor of the polymerization. An initial complex in the ground state between the phenothiazine and the triphenylsulfonium was formed prior to the excitation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…It was demonstrated that MTEMPO controlled the propagating radical at the chain end as well as the MTEMPO-mediated thermal polymerization based on the fact that the resulting polymer had the MTEMPO moiety at the chain end [11]. The electron transfer from MTEMPO to the onium salt has not been directly proved, however, this mechanism is supported by many electron transfer reactions from the electron donors to the onium salts [27][28][29] and by the electrochemical potentials of TEMPO [30][31][32] and the onium salts [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that MTEMPO controlled the propagating radical at the chain end as well as the MTEMPO-mediated thermal polymerization based on the fact that the resulting polymer had the MTEMPO moiety at the chain end [11]. The electron transfer from MTEMPO to the onium salt has not been directly proved, however, this mechanism is supported by many electron transfer reactions from the electron donors to the onium salts [27][28][29] and by the electrochemical potentials of TEMPO [30][31][32] and the onium salts [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The solution was thoroughly deoxygenated by bubbling oxygen-free nitrogen. The dilatometer was constructed by attaching two capillaries (internal diameter 0.18 cm) to a cylindrical reaction vessel (internal diameter 2.2 cm, volume 8 mL), which was placed in a constant temperature bath (30.00 ± 0.01 o C) in front of the irradiation source.…”
Section: Photopolymerization Proceduresmentioning
confidence: 99%
“…24 After the formation of the cation radical of perylene Pery +• only a fraction of the sensitizer is regenerated (the rest will be bound to the polymer, as proved by the presence of perylene groups in the UV spectrum of the polymer), whereas the sulphonium radicals that are not involved in the electron back-transfer are decomposed forming diphenylsulphide and phenyl radicals. 24,17 The presence of larger concentrations of sulphonium salt will result in the formation of additional initiating species due to the photolysis of both the ground state complex [Pery … S + ] o and the non-complexed sensitizer, therefore increasing the polymerization rate. …”
Section: Polymerization Mechanismmentioning
confidence: 99%
See 2 more Smart Citations